Application of Financial Flow Simulator (eSOSView™) for Analyzing Financial Viability and Developing a Sustainable Fecal Sludge Management Business Model in Kushtia, Bangladesh - Akbar Chinna Mohideen, Sheik Mohammed Shibl; Singh, Shirish; Chowdhury, Tanvir Ahamed; Brdjanovic, Damir (Frontiers in Environmental Science, 2022)
To achieve SDG 6.2.1 (a) on safely managed sanitation services, several financial flow models (FFMs) and business models for the sanitation value chain have been implemented in Bangladesh and elsewhere; however, there is limited research on financial viability and sustainability of business models. Bangladesh has attained 99% sanitation coverage, mostly with onsite sanitation systems; however, the country is facing a second-generation sanitation challenge, fecal sludge management, encompassing the entire sanitation chain. Kushtia Municipality in Bangladesh is entirely served by onsite systems; the fecal sludge emptying service is provided by the municipality, and the fecal sludge treatment plant is managed by a private entity. This study investigated sustainability of FFMs in Kushtia by using the financial, institutional, environmental, technical, and social (FIETS) sustainability approach and applying the financial flow simulator (eSOSView™) tool to analyze financial viability. Several criteria in each aspect of the FIETS approach were developed, scored, and validated by stakeholders to determine sustainability. The study found that the financial aspect is the most important criteria for sustainability and “modified parallel tax and discharge fee” is the most sustainable business model for Kushtia.